Current Knowledge on Osteoporosis Among Women in Muang District of Phitsanulok - Sookpeng, Supawitoo (Asian Health, Science and Technology Reports, 2006)
This study aimed to assess women’s knowledge on osteoporosis. The knowledge was assessed by an osteoporosis quiz composed of eighteen questions which were categorized into three subgroups: general knowledge on osteoporosis, risk factors associated with osteoporosis, preventive behavior and treatment of osteoporosis. One hundred and eighty four women from Phitsanulok, aged from 40 to 79 years old, were asked to complete questionnaires and the osteoporosis quizes. The total score on the osteoporosis quizes was 18 and the mean score obtained in this study was 13.46 (SD= 2.18; range = 8 to 18). Significant differences were found between respondents who had previously received information on osteoporosis and those who had not (mean score of 14.22+1.90 and 12.16+1.97,respectively; p<0.001), and between postmenopausal and premenopausal women (mean score of 13.16+2.33 and 13.87+1.88,respectively; p=0.028). There was a strong correlation between years of education and knowledge on osteoporosis (r=0.590, p=0.01). The findings indicated that women had less knowledge of risk factors associated with osteoporosis than general knowledge on osteoporosis as well as preventive behavior and treatment of osteoporosis. Thus, future planning for health education campaigns should target on people at higher risk for osteoporosis focusing especially on education of risk factors associated with the condition.